2013
DOI: 10.1539/joh.12-0150-oa
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Injury Proneness in Young Workers: A Survey in Stone Quarries

Abstract: Occupational Injury Proneness in Young Workers: A Survey in Stone Quarries: Asim SAHA, et al. Regional Occupational Health Centre (Eastern), India— Objectives Workplace injuries are of concern in adolescent and child workers. The factors of such injuries are important for injury prevention. This study explored the predictors of injury in such workers. Methods This study was carried out in stone quarries and included 147 children and adolescent workers (81 males and 66 females). The mean age of the subjects was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
9
2
1
Order By: Relevance
“…However, our finding was higher than the study done in Norway 31.70% [44], Brazil 5.6% [45], Nigeria 13.5% [46], and Turkey 28.7% [47]. Likewise, the pooled prevalence was lower than the study done in Japan 44.20% [48], India 49.70% [49], Iran 75.4% [50], Egypt 46.2% [51], Colombo 43.7% [52], Zimbabwe 41% [53] Greek 2.4% [54]. This can be possibly justified by that workrelated injury occur in low-and middle-income countries with the highest proportion of the world's population and the highest proportion of workers in risky jobs; whereas high-income countries also account for a significant number of work-related deaths [43].…”
Section: Discussioncontrasting
confidence: 84%
“…However, our finding was higher than the study done in Norway 31.70% [44], Brazil 5.6% [45], Nigeria 13.5% [46], and Turkey 28.7% [47]. Likewise, the pooled prevalence was lower than the study done in Japan 44.20% [48], India 49.70% [49], Iran 75.4% [50], Egypt 46.2% [51], Colombo 43.7% [52], Zimbabwe 41% [53] Greek 2.4% [54]. This can be possibly justified by that workrelated injury occur in low-and middle-income countries with the highest proportion of the world's population and the highest proportion of workers in risky jobs; whereas high-income countries also account for a significant number of work-related deaths [43].…”
Section: Discussioncontrasting
confidence: 84%
“…17,18 Various population based surveys have shown positive associations between musculoskeletal disorders and work factors like awkward postures, high physical exertion and vibration. 19 The risk of developing musculoskeletal disorders from an activity depends on frequency, duration and physical demands of the activity as also reported by ILO. 4 Two focus group discussions revealed that lack of time to take rest, to attend to personal health problems, social programs, less time for relaxations, low wage, poor attitude of employer and these were similarly observed in other studies also.…”
Section: Discussionmentioning
confidence: 71%
“…Five of the papers explored mining, specifically mining involving stone polishing and silicosis in Brazil [ 28 ]; small-scale or artisanal mining, whether for various minerals or gold [ 29 31 ]; or stone quarries [ 32 ]. Similar adverse health outcome categories as in the agricultural sector were reported in the mining sector, including injury, abuse, mortality, and loss of education.…”
Section: Resultsmentioning
confidence: 99%